Meningkatkan Kemampuan Membaca Al-Qur’an Melalui Metode Tahfizh di PAUD Fithri Desa Teluk Pulai Dalam Kualuh Leidong - Aziz, Mursal; Napitupulu, Dedi Sahputra; Mahdalena (UIR PRESS, 2024)
Reading the Koran is one of the lessons given to young children to develop children's religious potential. The aim of this research is to describe the process of improving the ability to read the Al-Qur'an through the tahfizh method at the Early Childhood Education School in Teluk Pulai Dalam Village, Kualuh Leidong. The research method in this research is Classroom Action research. The tahfizh method used by Fithri PAUD teachers in Teluk Pulai Dalam Village little by little, with regular repetition, young children at Fithri PAUD are starting to be able to memorize one, two or three short surahs as taught by their teachers in class. Based on Classroom Action Research conducted in cycle I, information was obtained that the level of student ability in cycle I was 18% in the fluent category, 29% in the moderate category, and 53% in the poor category. After carrying out the second cycle using the Tahfizh Method, information was obtained that the level of students' ability in the second cycle was 53% in the fluent category, 29% in the moderate category, and 18% in the poor category, after carrying out the third cycle, the level of students' ability in the third cycle was 82% in the fluent category, the medium category is 18% while the less category is 0%. This shows that the Tahfizh method has a significant influence in improving the ability to read the Koran in Fithri PAUD Teluk Pulai Dalam Village, Kualuh Leidong